Exploring the utility of bioaerosol metagenomics compared to PCRs for swine pathogen surveillance - Muwonge, Adrian; Gerber, Priscilla F.; Wee, Bryan A.; Thomson, Jill; Wang, Jingjing; Halbur, Patrick G.; Opriessnig, Tanja (Frontiers in Microbiomes, 2024)
IntroductionPathogen introduction and transmission at the farm, regional, or national level are associated with reduced animal welfare and negative impacts on herd economics. Ongoing infectious disease surveillance, active or passive, is therefore of high importance. For optimal resolution, each pig is sampled individually, for example by collecting blood or nasal swabs. In recent years, oral fluids have become very useful for population surveillance at the pen level. Another alternative is sampling the air to capture pathogens circulating across the entire barn via bioaerosols.ObjectiveThis study aimed to examine the potential utility of bioaerosol metagenomics for pathogen detection on pig farms.MethodsBioaerosols via automated air sampler, and oral fluid via pen-based ropes, were collected from each of two Scottish indoor pig farms. All samples were subjected to conventional routine bacterial isolation. Total genomic nucleic acids were extracted for PCR screening for three pig DNA viruses, three bacterial Mycoplasma species and an RNA virus. Illumina shotgun metagenomic sequencing was also conducted.ResultsOral fluids contained more DNA compared to bioaerosol samples. DNA integrity exhibited limited impact on PCR or sequence yield. While Streptococcus suis could be cultured from a single oral fluid sample, reads mapped to S. suis were detectable in all metagenomic samples. Other bacterial pig pathogens, including Mycoplasma hyorhinis, M. hyopneumoniae and M. hyosynoviae, were detected in oral fluid and aerosols by PCR and metagenomics. One of the two farms was PRRSV positive, and the virus was detectable via PCR in oral fluids but not in bioaerosols. Antimicrobial resistance (AMR) gene profiles had less variation between bioaerosols and oral fluids. Some identified AMR genes had strikingly similar abundance overall.ConclusionOverall, these findings indicate that there is potential utility of bioaerosol metagenomics for pathogen surveillance on pig farms; however, more research is needed for technical and cost optimization to allow for routine pathogen detection on livestock farms.